Eucalyptus urograndis seedlings production with composted agro-industrial waste and sewage sludge - Silva, F. A. M. [UNESP]; Zanon, J. A. [UNESP]; Nunes, G. M. [UNESP]; Silva, R. B. [UNESP]; Damatto Junior, E. R.; Tellez, F. A.; Rodriguez, A. M.; Sancho, I. M.; Robinson, M. V.; RuizAltisent, M.; Ballesteros, F. R.; Hernando, ECC (Fundacion General Univ Politecnica Madrid, 2014)
The purpose of this study was: evaluate the use of organic composts from agro-industrial residues of palm hearth and sewage sludge with different levels of fertilizer, as substrate for production of Eucalyptus urograndis seedlings; and compare the sewage sludge substrates with commercial substrate. We used a completely randomized design (CRD) in factorial 3 x 4, 3 substrates: Sewage sludge + Bark palm hearth (1: 1 v: v); Sludge + Bark palm hearth (1: 2 v: v); Sewage Sludge + Bark palm hearth (1: 3 v: v) and 4 levels (0, 2.0, 4.0 and 6.0 g dm(-3)) of fertilizer (N-P2O5-K2O - 09/12/15), and commercial substrate). Were measured: leaves number (NL), diameter (D), plant height (H), H / D ratio, Dickson quality index (IQD), dry biomass and root dry biomass. Among the substrates tested, the use of SI, composed sewage sludge + shell put 1: 1 v: v, resulted in the production of eucalyptus seedlings with better quality; Increased doses of granulated fertilizer resulted in significant effects on quality seedlings, being economically viable use of the dose 2.0 g L this fertilizer; substrates SI and SIII were presented promising results for the species tested, with performance equal or best to the commercial substrate. The use of sewage sludge and bark palm hearth presents viability as substrate in the production of eucalyptus seedlings and should be evaluated its use with other species.
Keywords: Eucalyptus urograndis; substrate; biosolid; seedling